1992
DOI: 10.1111/j.1467-8667.1992.tb00417.x
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Simulating Human Behavior During Emergency Evacuation Based on Classificatory Reasoning and Certainty Value Handling

Abstract: A computational model that simulates human behavior under fire and earthquake emergencies has been developed, using the object‐oriented language Smalltalk‐80. The present model consists of a space model, a scenario model and a human model. In the space model, the spaces in which people can move are represented by nodes connected by links. The nodes incorporate exit, guidelight and staircase facility data. Also, they feature environmental data including the darkness of the lighting system and the density of smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…A discrete and simple forerunner of this model was proposed by Gipps and Marksjö (1985). I also like to mention recent cellular automata of pedestrian dynamics (Bolay, 1998;Adler, 1998, 1999;Fukui and Ishibashi, 1999a, b;Muramatsu and Nagatani, 2000a, b;Klüpfel et al, 2000;Burstedde et al, 2001), emergency and evacuation models (Drager et al, 1992;Ebihara et al, 1992;Ketchell et al, 1993;Okazaki and Matsushita, 1993;Still, 1993Still, , 2000Thomson and Marchant, 1993;Løvås, 1998;Hamacher and Tjandra, 2000;Klüpfel et al, 2000), and AI-based models (Gopal and Smith, 1990;Reynolds, 1994Reynolds, , 1999Schelhorn et al1999).…”
Section: Pedestrian Trafficmentioning
confidence: 99%
“…A discrete and simple forerunner of this model was proposed by Gipps and Marksjö (1985). I also like to mention recent cellular automata of pedestrian dynamics (Bolay, 1998;Adler, 1998, 1999;Fukui and Ishibashi, 1999a, b;Muramatsu and Nagatani, 2000a, b;Klüpfel et al, 2000;Burstedde et al, 2001), emergency and evacuation models (Drager et al, 1992;Ebihara et al, 1992;Ketchell et al, 1993;Okazaki and Matsushita, 1993;Still, 1993Still, , 2000Thomson and Marchant, 1993;Løvås, 1998;Hamacher and Tjandra, 2000;Klüpfel et al, 2000), and AI-based models (Gopal and Smith, 1990;Reynolds, 1994Reynolds, , 1999Schelhorn et al1999).…”
Section: Pedestrian Trafficmentioning
confidence: 99%
“…Unfortunately, the frequency of such disasters is increasing (see Table 2), as growing population densities combined with easier transportation lead to greater mass events like pop concerts, sport events, and demonstrations. Nevertheless, systematic empirical studies of panic [75,90] are rare [76,77,79], and there is a scarcity of quantitative theories capable of predicting crowd dynamics at extreme densities [32,63,64,67,68,71]. The following features appear to be typical [57,91] 1.…”
Section: Situations Of "Panic"mentioning
confidence: 99%
“…Computer models have been also developed for emergency and evacuation situations [32,63,64,65,66,67,68,69,70,71]. Most research into panic, however, has been of empirical nature (see, e.g.…”
Section: Evacuation and Panic Researchmentioning
confidence: 99%
“…The material and literature on evacuations in general and the contraflow problem in particular have been published from various domains including social and behavioral sciences, transportation, and mathematics [5,4]. A survey by [22] of evacuation issues and contraflow revealed that planners have no recognized standards or guidelines for the design, operation, and location of contraflow segments.…”
Section: Related Workmentioning
confidence: 99%